Using Mass Communication Theory; Cognitive Switching: A Behavioral Trace of Human Information Processing for Television Newscasts; Attitudes of Scientists and Journalists Toward Media Coverage of Science News - Larry Meiller; William Tedrick (Journal of Applied Communications, 1979)
Reviews of Using Mass Communication Theory, by M.E. McCombs and L.B. Becker; "Cognitive Switching: A Behavioral Trace of Human Information Processing for Television Newscasts," by Thomas A. McCain and Mark G. Ross; "Attitudes of Scientists and Journalists Toward Media Coverage of Science News," by Michael Ryan.